REPRESENTASI PEREMPUAN PRIBUMI DALAM NOVEL RASINA KARYA IKSAKA BANU - Nina Nursintawati; Asep Firdaus; Fauziah Suparman (Media Bina Ilmiah, 2024)
This research aims to describe how forms of gender injustice are represented in the novel Rasina by Iksaka Banu and how the role of hegemonic power continues to perpetuate gender inequality in the position of indigenous women using feminist and postcolonial approach. The research method used is descriptive qualitative. The research results show that indigenous women experience forms of gender injustice in the form of identity marginalization, physical, psychological, and sexual violence, and a double burden experienced physically and mentally. Gender inequality cannot be separated from the existence of a patriarchal system. The depiction of power in the novel Rasina by Iksaka, apart from the patriarchal system that works, colonialism plays a role in strengthening dual power. Power hegemony plays a role in perpetuating gender inequality in the position of indigenous women in the novel Rasina by Iksaka Banu, described in aspects of social class structure and the legal policy system. The author describes one of the reflections of resistance carried out by indigenous women figures through writing.